The Effect of Workload on Turnover Intention Mediated by Job Satisfaction on Employees of PT PLN (Persero) Malang - Ajeng Dwi Anggraini; Sandra Irawati; Ratya Shafira Arifiani (Jurnal Manajemen Bisnis dan Kewirausahaan (JAMANIKA), 2022)
This study aims to determine how the influence of workload on turnover intention with job satisfaction as a mediator at PT. PLN (Persero) UPT Malang. The type of research used is explanatory research with a quantitative approach. The number of samples used in this study amounted to 50 people using the census sampling technique. Data was collected using a questionnaire. The data analysis technique used is path analysis. The results of this study indicate that: (1) workload has a significant effect on turnover intention. (2) workload has no significant effect on job satisfaction. (3) job satisfaction has no significant effect on turnover intention. (4) job satisfaction is not able to mediate the effect of workload on turnover intention.